Drama Techniques in ELT - Krčálová, Eliška (Univerzita Pardubice, 2020)
This master thesis is concerned with the use of drama techniques in ELT of young learners. The first chapter of the theoretical part depicts lifelong learning with a special focus on non-formal education. The second chapter defines young learners, their second language acquisition, and describes communicative competence and language skills related to the target group of learners. The third chapter of the theoretical part deals with the concept of drama, drama techniques and their potential for the application in ELT. The last chapter summarises the theoretical outcomes for the purposes of the research. The practical part is based on the qualitatively oriented case study which aims at a detailed description of implemented drama techniques within the non-formal context of ELT, and it further aims at a critical evaluation of the implementation process with regards to providing opportunities for communicative competence development of young learners.
Dramatické techniky ve výuce anglického jazyka
Keywords: drama; dramatické techniky; žáci mladšího školního věku; řečové dovednosti; komunikační kompetence; případová studie; drama; drama techniques; young learners; language skills; communicative competence; case study